Q. 34.4( 101 Votes )

In Fig. 6.58, ABC

Answer :

Using Pythagoras theorem in ΔADB, we get:

AB2 = AD2 + DB2 (i)

Applying Pythagoras theorem in ΔACD, we obtain

AC2 = AD2 + DC2

AC2 = AD2 + (DB + BC)2

AC2 = AD2 + DB2 + BC2 + 2DB x BC

AC2 = AB2 + BC2+ 2DB x BC [Using equation (i)]

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

In Fig. 3,<Mathematics - Board Papers